Smart Education Stacked Layers for AI-Informed Networked Learning - Duin, Ann; Tham, Jason; Campbell, Jessica; Ranade, Nupoor; Verhulsdonck, Gustav; Hocutt, Daniel; Pedersen, Isabel (Proceedings of the International Conference on Networked Learning, 2026)
This workshop is designed for program leaders, instructional specialists, and scholars interested in building a smart education system and exploring critical questions about human-centered design, design justice, and human-in-the-loop approaches in AI-informed networked learning. The workshop will solicit deep engagement with critical questions, inspire creativity, and empower participants to design and implement the smart education system using their activity worksheet as a strategic guide.